Upływający czas archeologii - Grzegorz Kiarszys (Przegląd Archeologiczny, 2013)
In this paper I consider the consequences of the use of different concepts of time in archaeology. I make an attempt to deconstruct our understanding of time in modern culture and find the ways in which it influences archaeological narratives. The common idea of time regarded as a universal and physical factor derives from the interpretation of Newtonian physics. It is also closely related to terms such as empiricism, inevitability and causation. In that interpretation linear time becomes a measure, and influences all occurring phenomena in an equal way. That understanding of time is frequently used by archaeologists for chronological ordering of artefacts. In fact it separates time from space. I argue that physical/universal time and time understood as the experience of a human being are completely different qualities. The first restrains the interest of archaeologists to evolutional variations of the physical forms of artefacts while the second approach allows us to interpret them through the prism of their cultural contents. Cultural time becomes meaning subjected to cultural rules instead of an objective measure that in the end lacks a time phenomenon